A study on the collection development practices of the Legislative Libraries of the Philippines House of the Representatives and the Senate - Austria, Carlo L.; Santos-Ong,Milagros (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
The study was conducted to determine the collection development practices of the Legislative libraries of the Philippine House of Representatives and the Senate, to determine the factors affecting collection development, and ultimately, to know if the said libraries, in effectively performing their responsibilities, contribute to the mandate of the Philippine Legislative branch.
The study carried out a descriptive survey method of inquiry. Survey questionnaires were handed out to the librarians of the libraries studied. A different type of survey questionnaires was handed out to several users of the two libraries studied. Interviews were also conducted.
The study revealed the factors that affect the collection development of the Legislative Libraries. These factors include but are not limited to: collection development policies, user needs, budgetary constraints, the physical size of the libraries and government bureaucracy. The study also revealed that the libraries contribute to the mandate of the Philippine Legislative Branch.
Recommendations include the provision of computerized database at the House of Representatives Legislative Library. It is also recommended that feasible studies be carried out with regard to the application of the library system utilized by the Senate Legislative Library to the House of Representative Legislative Library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Law libraries -- Collection development -- Philippines; Libraries -- User satisfaction -- Philippines; Philippines. House of the Representatives Legislative Library; Philippines. Senate Legislative Library